2023
DOI: 10.1155/2023/6329873
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipid Profile and Its Relative Ratios (Cholesterol/HDL-C, Triglyceride/HDL-C, LDL-C/HDL-C, WBC/HDL-C, and FBG/HDL-C) on Admission Predicts In-Hospital Mortality COVID-19

Abstract: Background. Lipid profile and its related ratios such as total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), TG/HDL-C ratio, TC/HDL-C ratio, LDL-C/HDL-C ratio, white blood cell (WBC)/HDL-C ratio, and fasting blood glucose (FBG)/HDL-C ratio are valuable indicators that have been studied in various disorders to predict mortality. The present study was conducted with the aim of investigating the role of lipid profile ratios in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…A modified metabolic aspect has been observed in many COVID-19 patients, and this includes blood lipid levels. HDL cholesterol has been associated with poorer outcomes and more severe cases [ 21 , 50 ]. It has been suggested that it is involved in the regulation of innate immune response through interaction with ABCA1 or ABCG1, which negatively regulates T-cell activation and the expression of inflammatory mediators [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A modified metabolic aspect has been observed in many COVID-19 patients, and this includes blood lipid levels. HDL cholesterol has been associated with poorer outcomes and more severe cases [ 21 , 50 ]. It has been suggested that it is involved in the regulation of innate immune response through interaction with ABCA1 or ABCG1, which negatively regulates T-cell activation and the expression of inflammatory mediators [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that hypoalbuminemia leads to oxidative stress with cellular damage and apoptosis. Together with albumin dosage, a low TC and lymphocyte count are also associated with higher mortality, reflecting a deterioration in nutritional status and a decreased immune and inflammatory status [ 26 , 27 ]. The CONUT score carried out at the moment of admission and represented a vicious cycle well; indeed, patients with multimorbidity tend to suffer malnutrition through many mechanisms, such as fluid retention, long bed stay, lack of appetite leading to inflammation, and neurohormonal activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…доказано, что у умерших пациентов значения ТГ, ОХ, ЛПНП и ЛПВП, а также соотношение ОХ/ЛПВП, ЛПНП/ЛПВП, ТГ/ЛПВП, лимфоциты/ЛПВП и моноциты/ЛПВП были достоверно ниже, а отношение лейкоциты/ЛПВП и гемоглобин/ЛПВП -выше, чем у выздоровевших пациентов. Доказана достоверная взаимосвязь оцениваемых параметров с неблагоприятными исходами заболевания COVID-19 [38].…”
Section: показатели липидного профиля как прогностические критерии тя...unclassified